Looking at the evolution of macroprudential policy stance: A growth-at-risk experiment with a semi-structural model - Louis Boucherie; Katarzyna Budnik; Jiri Panos (European Central Bank (ECB), 2022)
This paper proposes a methodology for measuring the macroprudential policy stance based on a distance-to-tail metric perspective. This approach employs a large-scale semi-structural model reflecting the dynamics of 91 significant euro area banks and 19 euro area economies and is presented through an assessment of the stance evolution for the aggregate euro area economy and for the individual euro area countries. Our results uncover mild tightening of the macroprudential policy stance before the end of 2019. This trend is abruptly interrupted at the onset of the Covid-19 pandemic but reappears at the end of 2020 before picking up again over the first half of 2021. Our assessment also reveals a marginal impact of the macro-financial policies applied, which is particularly notable throughout 2020.
Keywords: E37; E58; G21; G28; 330; macroprudential policy; macroprudential policy stance; distance-to-tailmetric; Growth-at-Risk; Lending-at-Risk